Introducing NFT Model as a pedagogy using Dale’s and Bloom’s Taxonomy: A complementary tool for learning instruction - Thusi, Nisi; Costa, King (My University, 2020)
Advanced pedagogy is the way to enhance teaching and learning performance for non-financial students. There are different methods in use across the globe for innovative teaching of higher learning students. The use of multimedia and technology empowers educational processes by increasing interaction between teachers and students. Hybrid teaching and blended learning follow an integrated approach to teaching that blends with students' interests and teacher's personality that needs curriculum-appropriate methods. This includes e-learning in addition to the face-to-face teaching that is customarily used in teaching . While teachers are still an authority figure in a student-centered teaching model, they both play an equally active role in the learning process. Teachers should thus apply themselves to utilizing innovative methods so that the students’ learning process is as free-flowing and that the methodology used creates an atmosphere adaptable to conducive learning environment. The application of innovative teaching and learning methods is critical if we are to motivate and enculturate a spirit of learning and cooperation by encouraging others and doing your share on the part of students. The role of education is to ensure that while academic personal are involve in active teaching, an effort is made to ensure alignment between what is taught and what is comprehensible in relation to students. Linguistically diverse, cultural backgrounds and the familiarity with the expected standards have profound effects on teaching methods. Students must frequently engage in collaborative learning activities such as selecting, organizing, locating, synthesizing and using relevant information sources to construct meaning about some particular knowledge. Such activities have been assumed to lead to higher levels of knowledge acquisition and learning. The goal of this study is an ongoing and progressive examine of how Edger Dale's Cone of Experience and Bloom's taxonomy is employed to positively influence student learning. In this conceptual research the methodology used was hinged on analytic processes for material already published in this area. Key variables under investigation forecast on integration of Dales and Blooms theories for theoretical perspectives with the researchers pedagogy known as the NFT. The researcher implemented the NFT pedagogy in an academic setting to non-financial student in a period of 12 months and observed positive results. The researcher anticipates that the findings of this study will contribute to the enhancement of both teaching-learning and assessment process, which hopefully will uplift the learner to learn at a deeper level in a manner that incorporates small-group learning, achieve higher grades, retain information longer, acquire greater communication and teamwork skills, and gain a better understanding of the module.
Keywords: Collective creativity; Collaborative Learning; Innovative teaching and learning; Teacher education and methodology.